Challenges and Opportunities for Smallholders in Banana Value Chains - Tinzaara, William; Ocimati, Walter; Kikulwe, Enoch; Otieno, Gloria (Achieving sustainable cultivation of bananas, 2018)
Bananas and plantains (Musa spp.) rank sixth on the list of staple crops in the world (FAO, 2017). With a global production of around 86 million tons per annum, about 18 million tons are exported, while the remainder is consumed domestically. Though exports, mainly comprising dessert bananas, account only for about 20% of global production, they account for about half of the value generated (about US$13 billion out of a total of US$26 billion). Cooking bananas and plantains account for the other half of the value generated and, given that they account for about 80% of global banana production, play a critical role in terms of global food security and in national and household economies.
Keywords: Opportunities; Smallholders; Banana